Validation of a Triplex Pharmacokinetic Assay for Simultaneous Quantitation of HIV-1 Broadly Neutralizing Antibodies PGT121, PGDM1400, and VRC07-523-LS - Wesley, Martina S.; Chiong, Kelvin T.; Seaton, Kelly E.; Arocena, Christine A.; Sawant, Sheetal; Hare, Jonathan; Hernandez, Kasey; Rojas, Michelle; Heptinstall, Jack; Beaumont, David; Crisafi, Katherine; Nkolola, Joseph; et al. (Frontiers in Immunology, 2021)
The outcome of the recent Antibody Mediated Prevention (AMP) trials that tested infusion of the broadly neutralizing antibody (bnAb) VRC01 provides proof of concept for blocking infection from sensitive HIV-1 strains. These results also open up the possibility that triple combinations of bnAbs such as PGT121, PGDM1400, as well as long-lasting LS variants such as VRC07-523 LS, have immunoprophylactic potential. PGT121 and PGDM1400 target the HIV-1 V3 and V2 glycan regions of the gp120 envelope proteins, respectively, while VRC07-523LS targets the HIV-1 CD4 binding site. These bnAbs demonstrate neutralization potency and complementary breadth of HIV-1 strain coverage. An important clinical trial outcome is the accurate measurement of in vivo concentrations of passively infused bnAbs to determine effective doses for therapy and/or prevention. Standardization and validation of this testing method is a key element for clinical studies as is the ability to simultaneously detect multiple bnAbs in a specific manner. Here we report the development of a sensitive, specific, accurate, and precise multiplexed microsphere-based assay that simultaneously quantifies the respective physiological concentrations of passively infused bnAbs in human serum to ultimately define the threshold needed for protection from HIV-1 infection.